2020
DOI: 10.31351/vol29iss2pp88-98
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of B-cyclodextrin Based Nanosponges of 5- Fluorouracil by Using Ultrasound Assisted Method

Abstract: CD-nanosponges were prepared by crosslinking B-CD with diphenylcarbonate (DPC) using ultrasound assisted technique. 5-FU was incorporated with NS by freeze drying, and the phase solubility study, complexation efficiency (CE) entrapment efficiency were performed. Also, the particle morphology was studied using SEM and AFM. The in-vitro release of 5-FU from the prepared nanosponges was carried out in 0.1N HCl. 5-FU nanosponges particle size was in the nano size. The optimum formula showed a particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
1
16
1
Order By: Relevance
“…Our study results indicated that 5-FU was not achieved the expected encapsulation with carbonate nanosponge in contradictory to the reported studies ( 32 34 ), this encouraged us to study the complexation of 5FU with the raw cyclodextrin to further explain the results. We also conducted preliminary phase solubility studies for both types of nanosponges and non- crosslinked cyclodextrin, all systems did not show changes in saturation solubility of 5-FU with increasing the level of cyclodextrin or the nanosponges, so we fully characterized and evaluated the complex and samples to clarify the results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study results indicated that 5-FU was not achieved the expected encapsulation with carbonate nanosponge in contradictory to the reported studies ( 32 34 ), this encouraged us to study the complexation of 5FU with the raw cyclodextrin to further explain the results. We also conducted preliminary phase solubility studies for both types of nanosponges and non- crosslinked cyclodextrin, all systems did not show changes in saturation solubility of 5-FU with increasing the level of cyclodextrin or the nanosponges, so we fully characterized and evaluated the complex and samples to clarify the results.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, a recent study has shown the development of a 5-FU complex with cyclodextrin polymer in an aqueous solution and suggested the formation of an unstable inclusion complex ( 29 ). Moreover, a recent study suggested that cyclodextrin-based nanosponge formulations may be a promising technique for the delivery of 5-FU ( 32 ). This contradiction in the published studies necessitates the reconsideration of the complexation of 5-FU with cyclodextrin.…”
Section: Discussionmentioning
confidence: 99%
“…For further crosslinking, the mixture must be incubated for a longer period ( Rezaei et al, 2021 ). At the end of the reaction a fine homogeneous powder is obtained ( Jasim et al, 2020 ; Moin et al, 2020 ; Sadjadi and Koohestani, 2021a , 2021b ; Srivastava et al, 2021 ). The powdered substance is repeatedly washed with water and/or acetone, and, generally, it is also subjected to Soxhlet extraction with ethanol or acetone, and even to an additional washing with sodium hydroxide (NaOH) solution ( Kumar A. and Rao R., 2021 ; Sadjadi and Koohestani, 2021a , 2021b ; Suvarna et al, 2021 ).…”
Section: Cyclodextrin-based Nanosponges: Synthesis and Propertiesmentioning
confidence: 99%
“…Therefore, it is essential to develop effective multifunctional 5-FU nanocarriers to improve targeted delivery, resulting in improved anticancer treatments. The following nanocarriers of 5-FU were proposed: polymer-based carriers such as chitosan beads, Eudragit ® , Poly(alkylcyanoacrylates), PLGA, β-cyclodextrin as well as liposomes, nanoemulsions, solid lipid nanoparticles, gold nanoparticles, silica nanocarriers, iron oxides nanoparticles, graphene oxides, and QD [24][25][26][27][28][29][30][31][32][33][34][35] The present contribution aimed to develop a novel method of preparing multifunctional 5-FU nanocarriers and their in vitro characterization. 5-FU polyaminoacid-based core@shell nanocarriers were formed by the encapsulation of drug-loaded nanocores with polyaminoacids multilayer shell via the layer-by-layer method with saturation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to develop effective multifunctional 5-FU nanocarriers to improve targeted delivery, resulting in improved anticancer treatments. The following nanocarriers of 5-FU were proposed: polymer-based carriers such as chitosan beads, Eudragit ® , Poly(alkylcyanoacrylates), PLGA, β-cyclodextrin as well as liposomes, nanoemulsions, solid lipid nanoparticles, gold nanoparticles, silica nanocarriers, iron oxides nanoparticles, graphene oxides, and QD [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]…”
Section: Introductionmentioning
confidence: 99%